A new soft-matter material with old chemistry: Passerini multicomponent polymerization-induced assembly of AIE-active double-helical polymers with rapid visible-light degradability. Issue 31 (28th July 2020) - Liu, Jupen; Luo, Zhonglong; Yu, Le; Zhang, Ping; Wei, Hongqiu; Yu, You
Abstract : Passerini multicomponent polymerization-induced assembly is reported to design a water-soluble, AIE-active, double-helical polymer with reversible multi-responsiveness to external stimuli and rapid visible-light degradability. Abstract : Mimicking the superstructures and functions of natural chiral materials is beneficial to understand specific biological activities in living organisms and broaden applications in the fields of chemistry and materials sciences. However, it is still a great challenge to construct water-soluble, double-helical polymers with multiple responsiveness. Herein, we report for the first time a straightforward, general strategy to address this issue by taking advantage of Passerini multicomponent polymerization-induced assembly (PMPIA). The polymerization-induced generation of supramolecular interactions in chiral α-acyloxy amides drives the assembly of polymers and improves their stability in various solvents. This double-helical polymer is sensitive to metal ions, temperature, pH, and solvents, making both the superstructure and the AIE effect reversibly adjustable. Meanwhile, the hydrogen-bonding-assisted cyclization of photolabile α-acyloxy amides accelerates the degradation of helical polymers under visible-light irradiation. It is anticipated that this novel PMPIA strategy opens new horizons to inspire the design of advanced chiral/helical polymers with multiple functions.